Analisis Terhadap Masalah Tindak Lanjut Laporan Akhir Pemeriksaan (LAHP)/Rekomendasi Ombudsman - Sitepu, Rajin; Syafitri, Isdiana (Universitas Ekasakti, 2024)
This research is motivated by the fact that there are still many LAHP and/or Ombudsman Recommendations that are not implemented, while the implementation is a necessity for the realization of good, clean and efficient public service delivery and to prevent and eliminate abuse of authority as specified in the laws and regulations. This research was conducted using secondary data, which is sourced from the 2021 Annual Report of the Ombudsman RI, Laws and Regulations on the Ombudsman and on Public Services. From the research conducted, it is known that the factors causing the LAHP and / or Ombudsman Recommendations not to be implemented are due to: First, the legal material factor which still contains legal loopholes, intertwined with the Second factor, namely Law Enforcement, where not all Officials who have the authority to enforce the law oversee the implementation of LAHP and / or Recommendations, as well as impose administrative sanctions on the Reported Party who does not implement LAHP and / or Recommendations, and Third, the factor of those affected by the rule of law, where there is still an assumption of some Reported Party, that LAHP and / or Recommendations are only suggestions, not as something that must be implemented.